Integrated well-being assessment in an appropriate-for-gestational-age (AGA) fetus and acute placentary insufficiency due to histological chorioamnionitis: Case report - Castillo-Urquiaga, Walter (2023)
Background. Acute placental uterine vascular insufficiency is a cause of adverse fetal outcome in fetuses with failure to reach their growth potential and are born at an appropriate weight for gestational age. Clinical case. A 24-year-old patient, 37 weeks gestational age, went to the National Maternal Perinatal Institute of Lima, Peru, for reporting little vaginal bleeding. In the clinical evaluation, a BP of 90/60 mmHg, uterine height 32 cm, fetal heartbeat was found in 152. At ultrasound evaluation, a fetus of 2902 grams (34 Hadlock percentile) was reported 1 hour after admission, a Profile Fetal biophysicist 6/8 due to decreased body movements, 11cm amniotic fluid index, grade III posterior fundic placenta, Middle Cerebral Artery Doppler of the 1.18, umbilical artery Doppler of the 0.56, ductus venosus Doppler 0.26 and Aortic Isthmus with absent diastole. The contraction stress test 3 hours after admission was scored 5 points with decreased fetal movements, decreased variability and absent accelerations. An emergency caesarean section was indicated obtaining a 2846 gr male newborn, size 47.5 cm, Apgar 8-9. Meconial fluid with a dark bloody appearance was found. At the parenchymal section, hairy infarcts: recent 10% and old 5%. Hypoplastic chorionic villi with wide intervillous spaces. Conclusions. Integrated surveillance of AEG growth fetuses allows to be detected those at risk of adverse outcome from acute placental insufficiency.